2018
DOI: 10.1063/1.5043239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface roughness on surface charge accumulation characteristics and surface flashover performance of alumina-filled epoxy resin spacers

Abstract: The accumulated charges on the insulator surface become a key factor to incur surface flashover. The charge accumulation process is closely related to the surface condition. This research investigates the effects of surface roughness on surface charge accumulation behavior and surface flashover performance of alumina-filled epoxy resin spacers in SF6/N2 mixtures under DC voltage. The insulator is prepared with only half surface subjected to rough treatment. The accumulated charges are distributed in two region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…However, besides the intrinsic properties of nanodielectrics, extrinsic surface properties were also found as important factors in our follow-up studies. Electrical properties are inevitably affected by surface conditions, including surface hydrophobicity [24][25][26][27][28]. In this paper, surface tracking measurements were conducted on nano-MgO/epoxy composite samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, besides the intrinsic properties of nanodielectrics, extrinsic surface properties were also found as important factors in our follow-up studies. Electrical properties are inevitably affected by surface conditions, including surface hydrophobicity [24][25][26][27][28]. In this paper, surface tracking measurements were conducted on nano-MgO/epoxy composite samples.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly accepted that physical scratching of the insulation surface from sandpaper could optimise its surface state [21, 22]. Given this, the insulation group EP sand prepared by the various scales of sandpaper exhibits a much higher roughness ( R a ) profile than that of the insulation groups EP pure and EP ion as justified in Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…It was obtained that the augmented surface conductivity due to the conversion of deep surface traps into shallow after modification accelerated the surface charge dissipation and carrier mobility which provide a more homogeneous E-field distribution and rise the flashover threshold. Similarly, it has been proved by many studies that surface polishing of spacers by roughness treatment can dramatically alter their surface condition leading to improved surface properties [21,22]. Studies [23][24][25][26] reveal that the surface flashover voltages in a vacuum can be augmented considerably after increasing the surface roughness of polymeric dielectrics.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Studies have shown that surface flashover of Al 2 O 3 /EP is closely related to the aggregation and dispersion behavior of surface charges at the gas-solid interface, and the movement characteristics of surface charges are influenced by various aspects such as the material morphology, elemental ingredients, and electrical parameters. [7][8][9] Low-temperature plasma technology is highly efficient, simple to operate, energysaving, and environment-friendly, and it can safely and efficiently regulate the gas-solid interface. 10,11 In plasma technology, the effect of plasma on the material surface can be divided into two categories: graft etching and polymer deposition, depending on the nature of the precursors and the impact on the material.…”
Section: Introductionmentioning
confidence: 99%